Design, development, and validation of a high‐throughput drug‐screening assay for targeting of human leukemia. Issue 4 (25th October 2013) - Karjalainen, Katja; Pasqualini, Renata; Cortes, Jorge E.; Kornblau, Steven M.; Lichtiger, Benjamin; O'Brien, Susan; Kantarjian, Hagop M.; Sidman, Richard L.; Arap, Wadih; Koivunen, Erkki
Abstract : BACKGROUND: The authors developed an ex vivo methodology to perform drug library screening against human leukemia. METHODS: The strategy for this screening relied on human blood or bone marrow cultures under hypoxia; under these conditions, leukemia cells deplete oxygen faster than normal cells, causing a hemoglobin oxygenation shift. Several advantages were observed: 1) partial recapitulation of the leukemia microenvironment, 2) use of native hemoglobin oxygenation as a real‐time sensor/reporter, 3) cost‐effectiveness, 4) species specificity, and 5) a format that enables high‐throughput screening. RESULTS: For a proof of concept, a chemical library (size, approximately 20, 000 compounds) was screened against human leukemia cells. Seventy compounds were identified ("hit" rate, 0.35%; Z‐factor = 0.71) that had activity, and 20 compounds were examined to identify 18 true‐positive compounds (90%). Finally, the results demonstrated that carbonohydraxonic diamide group‐containing compounds are potent antileukemia agents that induce cell death in leukemia cells and in patient‐derived samples. CONCLUSIONS: The current results indicated that this unique functional assay can identify novel drug candidates and can help with the development of future applications in personalized drug selection for patients with leukemia. Cancer 2014;120:589–602 . © 2013 American Cancer Society . Abstract : It is fundamental to develop screening platforms that can assess the therapeutic relevance of drug candidates within the appropriate disease microenvironment. Therefore, the authors have developed a new functional screening assay that identifies potential antileukemia agents in the presence of human blood or bone marrow.